Agricultural credit legislation : a preliminary survey in selected developing countries - Mylonas, D.; Food and Agriculture Organization of the United Nations (Rome : Food and Agriculture Organization of the United Nations, 1974)
The purpose of this study is to identify, in the light of an analysis of the legislative texts of certain developing countries, the fundamental lines followed by the different legal systems governing agricultural credit.
Includes bibliographical references: p. 134-135.
ne 16/04/2019
Ref
Keywords: Agricultural credit